The Implementation of Education Policy in the Development of Islamic Religious Education in the Industrial Revolution Era 4.0 - Adisel, Adisel; Thadi, Robeet; Suryati, Suryati (Madania: Jurnal Kajian Keislaman, 2022)
The implementation of Islamic school management policies is important, keep in mind that there are still many educational issues of concern, especially regarding ethics and other values. The training strategy adds to the improvements in the implementation of the main Islamic Religious Education (PAI) learning. This research is expected to find out how the implementation of policies regarding the establishment of Islamic schools is carried out in the 4.0 era. Research attempts to reveal instructional arrangements in improving PAI learning in the 4.0 era which have been carried out by involving a subjective approach as a method of checking to produce information that has novelty. This research method uses a qualitative descriptive approach with literature study. As a result, the transformation of Islamic education is used to find a way out of the problems that occur, thus strengthening Islamic educational institutions and the need for quality management quality improvements, effective leadership, and the need to reform educational policies, so that they are able to compete and the results can create creative, innovative, possessing human beings. Good character, independence, love for the motherland and religion in order to become a stronghold in the era of the industrial revolution 4.0 where in this era human resources are required to be fast, precise, attractive and productive. Implementasi penerapan kebijakan pengelolaan sekolah Islam penting, mengingat masih banyak masalah pendidikan yang memperihatinkan terutama tentang etika dan tata nila lainnya. Strategi pelatihan menambah perbaikan dalam implementasi pembelajaran Pendidikan Agama Islam (PAI) yang utama. Penelitian ini diharapkan dapat menemukan bagaimana pelaksanaan implementasi kebijakan mengenai pendirian sekolah Islam di era 4.0. Penelitian berusaha mengungkapkan penyusunan instruksional dalam peningkatan pembelajaran PAI di era 4.0 yang telah dilakukan dengan melibatkan pendekatan subjektif sebagai metode pemeriksaan menghasilkan informasi yang memiliki kebaruan. Metode penelitian ini menggunakan pendekatan diskriptif kualitatif dengan studi pustaka. Hasilnya pentransformasian pendidikan Islam digunakan untuk menemukan jalan keluar dari masalah yang terjadi, sehingga menguatkan lembaga pendidikan Islam serta diperlukannya perbaikan kualitas manajemen yang bermutu, kepemimpinan yang efektif, serta perlunya mereformasi kebijakan pendidikan, sehingga mampu bersaing dan hasilnya dapat mewujudkan manusia kreatif, inovatif, memiliki karakter baik, mandiri, cinta tanah air dan religius guna menjadi benteng di era revolusi industri 4.0 yang mana dalam era ini sumber daya manusia dituntut menjadi sumber daya cepat, tepat, menarik, dan produktif,